Divergent and linked selection shape patterns of genomic differentiation between European and North American Atlantic salmon (Salmo salar). Issue 12 (21st June 2020) - Lehnert, Sarah J.; Kess, Tony; Bentzen, Paul; Clément, Marie; Bradbury, Ian R.
Abstract: As populations diverge many processes can shape genomic patterns of differentiation. Regions of high differentiation can arise due to divergent selection acting on selected loci, genetic hitchhiking of nearby loci, or through repeated selection against deleterious alleles (linked background selection); this divergence may then be further elevated in regions of reduced recombination. Atlantic salmon ( Salmo salar ) from Europe and North America diverged >600, 000 years ago and despite some evidence of secondary contact, the majority of genetic data indicate substantial divergence between lineages. This deep divergence with potential gene flow provides an opportunity to investigate the role of different mechanisms that shape the genomic landscape during early speciation. Here, using 184, 295 single nucleotide polymorphisms (SNPs) and 80 populations, we investigate the genomic landscape of differentiation across the Atlantic Ocean with a focus on highly differentiated regions and the processes shaping them. We found evidence of high (mean F ST = 0.26) and heterogeneous genomic differentiation between continents. Genomic regions associated with high trans‐Atlantic differentiation ranged in size from single loci (SNPs) within important genes to large regions (1–3 Mbp ) on four chromosomes (Ssa06, Ssa13, Ssa16 and Ssa19). These regions showed signatures consistent with selection, including high linkage disequilibrium, despite no significant reduction in recombination. Genes and functional enrichment of processes associated with differentiated regions may highlight continental differences in ocean navigation and parasite resistance. Our results provide insight into potential mechanisms underlying differences between continents, and evidence of near‐fixed and potentially adaptive trans‐Atlantic differences concurrent with a background of high genome‐wide differentiation supports subspecies designation in Atlantic salmon.